Enhancing Propulsion Performance for Container Ships through Propeller Adjustments: A Case Study MV. Kendhaga Nusantara 6 - Ariany, Zulfaidah; Santoso, Budi; Suharto, Suharto; Sarwoko, Sarwoko (Department of Naval Architecture - Diponegoro University, 2023)
The ship's service speed performance is prioritized in a ship's propulsion system planning. Motor Vessel. KENDHANGA NUSANTARA 6 is a type of containerized cargo ship built to support the sea toll program in the Tanjung Emas port area, Semarang. The less significant propeller pitch affects the ship's ability to move. The experiment was carried out by operating the machine with maximum capability. The phenomenon of the geometric shape of the propeller provides information on the rotation results and the distribution of the working forces. The structure of the propeller design describes the ability and level of effectiveness when the propeller is submerged in water. The results of this study show that the optimization value of the right propeller pitch is 0.6%, the pitch width is 1660 mm, and the optimization value of the left propeller pitch is 1.2% with a pitch width of 1670 mm; this value can make the ship's rate speed during the docking trial 12.3 knots, following the planned speed.